Influence of NUDT15 Genotyping on Dose Intensity of Thiopurine Administration and Long-Term Clinical Outcomes (Hospitalization and Surgery) - Tsunoda, Shotaro; Kojima, Yuichiro; Hirotsu, Yosuke; Amano, Hiroyuki; Miura, Yuko; Ashizawa, Hiroshi; Ohyama, Hiroshi; Hosoda, Kenji; Suzuki, Yoji; Mochizuki, Hitoshi; et al. (Archives of Clinical and Biomedical Research, 2024)
Background: Thiopurines are one of the major drugs for treatment of inflammatory bowel disease. It is well known that SNPs in TPMT are the main cause of leucopenia and hair loss in European descent. In Asian individuals, the SNP p.Arg139Cys in exon 3 of NUDT15 is associated with leucopenia and hair loss. Previously, we demonstrated that thiopurineinduced leucopenia is related not only to exon 3 but also exon 1 SNPs in a cohort followed for a short term. The aim of this study was to evaluate the long-term effects of NUDT15 on clinical outcomes. Methods: Patients (ulcerative colitis130 cases, Crohn’s disease 55 cases) were divided into mutation and wild-type NUDT15 groups, and the daily dosage of thiopurines and the effect of mutation on hospitalization and surgery were retrospectively investigated over a long period of up to 10 years (median, 7.8 years). Results: Regarding TPMT SNPs, p. Pro80Ala, p. Thy154Ala and p. Tyr240Cys were not detected, and all genes were wild-type. Compared to the NUDT15 mutation group (n = 48), the daily thiopurine dosage was increased in the wild-type group (n = 137) (p = 0.024). The time to dose reduction and discontinuation of thiopurines was significantly shorter in the NUDT15 mutation group (p < 0.001, p = 0.039). The NUDT15 mutation group tended to have more hospitalizations (p = 0.067), and surgeries were significantly more frequent (p = 0.028). In ulcerative colitis patients, thiopurine discontinuation was associated with hospitalization and surgery (p = 0.003, HR 2.87, 95% CI 1.44-5.71, p = 0.036, HR 5.45, 95% CI 1.12-26.5). In Crohn's disease patients, the presence of SNPs was associated with hospitalization (p = 0.019, HR 3.68, 95% CI 1.24-10.97) and surgery (p = 0.036, HR 6.81, 95% CI 1.14-40.86). Conclusions: The presence of the NUDT15 mutation affects maintenance of thiopurine dosage in the long term. In ulcerative colitis, it is important to continue thiopurines with fine-tuning of the dosage to avoid hospitalization and surgery. In Crohn's disease, a direct association between NUDT15 SNPs and hospitalization and surgery was found.